Hyperrealitas Tradisi Lisan Dalam Pencegahan Penyimpangan Sosial Dikawasan Wisata Danau Lau Kawar Kabupaten Karo - Dedi Andriansyah; Siti wardani Nur Azmi; Elvirida Lady Angel Purba; Fadinda Aisyah; Yola Claudia (Mahesa Research Center, 2023)
This research aims to explore the telling of the story of the Legend of Nini Kawar at the Lake Lau Kawar tourist attraction, explore the local community's strategy in bringing the existence of the Nini Kawar story to tourists in an analysis of Jean Baudrillard's hyperreality in the Lake Lau Kawar tourist area and explore the implications of telling the story of Nini Kawar in preventing deviations. social activities carried out by tourists in the Lake Lau Kawar tourist area, Karo Regency. This research uses an embedded mixed-method design that combines qualitative and quantitative data searches. The data sources in this research are the results of participant observation, ethnographic interviews, and distribution of questionnaires. The data analysis techniques used are ethnographic interview analysis, domain analysis, and component analysis which will be assisted by the atlas. ti application. Meanwhile, the questionnaire on the third problem formulation data will be measured using percentage analysis and assisted with the SPSS application. This research was conducted in Kuta Gugung, Naman Teran District, Karo Regency, North Sumatra. The results of this research found that Nini Kawar or Nini Karo is a figure believed by people in the Lau Kawar Lake tourist area to be the guardian of Lau Kawar Lake. The legend of Nini Kawar is still kept alive in the Lau Kawar Lake area. The aim of reviving Lake Lau Kawar is to socially control the behavior of the community and tourists who visit the Lake Lau Kawar area. This can be seen from the existence of prohibitions or taboos that visitors must obey. These prohibitions and taboos must be obeyed by the local community and visitors who come to the area to avoid the plague of Nini Kawar